2013
DOI: 10.1080/00222895.2012.760513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Scale Development, Reliability for Sitting and Standing From the Chair for Duchenne Muscular Dystrophy

Abstract: The authors aimed to (a) develop a scale to evaluate non-wheelchair-dependent children with Duchenne muscular dystrophy (DMD) while sitting and standing from the chair, (b) test its reliability, and (c) correlate the scores of this scale with the time, the age and the Vignos. Thirty DMD boys performed sit-to-stand and stand-to-sit from the chair 4 times. Scale development was based on a previous movement characterization in healthy children and in DMD children and on suggestions by physical therapists with exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
0
17
0
14
Order By: Relevance
“…The child can let himself fall on the chair during the trunk flexion phase. A previous study showed that the absence of trunk flexion (contact phase) and trunk extension (extension phase) was due to impaired eccentric muscle contraction 7 . As well, patients performed compensatory movements, such as upper limb support and trunk rotation and lateral tilting 7 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The child can let himself fall on the chair during the trunk flexion phase. A previous study showed that the absence of trunk flexion (contact phase) and trunk extension (extension phase) was due to impaired eccentric muscle contraction 7 . As well, patients performed compensatory movements, such as upper limb support and trunk rotation and lateral tilting 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the absence of trunk flexion (contact phase) and trunk extension (extension phase) was due to impaired eccentric muscle contraction 7 . As well, patients performed compensatory movements, such as upper limb support and trunk rotation and lateral tilting 7 . In sit-to-stand, a progressive increase of the base of support with trunk flexion and rotation and upper limb support on the seat were observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations